Evaluation of embedding learning tool of active and passive fire safety system for undergraduate studies via experts / Khairilmizal Samsudin ... [et al.] - Samsudin, Khairilmizal; Mohamad Hatta, Nur Ezzate; Kassim, Zakaria; Che Azid, Md Khairul Azuan; Mohamed Noor, Mohd Aminorddin Darus; Hussin, Mohamad Fahmi; Kamarudin, Ainul Husna; Kasri, Mohd Haikal (UiTM Press, 2023)
Challenges are faced by students during the learning process of the fire safety subject. Different learning styles possessed by the students require diverse teaching approaches to facilitate their understanding of active and passive fire safety system interconnection. With the pandemic COVID-19 outbreak both educator and learners now faced difficulties in the teaching and learning process of fire safety courses which need to be delivered virtually. This study aimed to develop a feasible learning tools for the active and passive fire safety systems and to validate the developed model of Fire Safety Interconnection multimedia in using it as an educational tool for fire safety subjects. The methodology were based on documentation review methods and the content is validated through concrete reference. Face validity methods were utilized to further validate the developed materials by using a survey questionnaire which functioned as a tool for the SMEs to validate the developed learning tools. With the developed learning tools developed, the results indicate that all SMEs are satisfied with the developed learning tools and it is suitable to be used as an educational instrument in fire safety subjects.